Nanopowder hydrogenation catalysts of diesel fraction components; IFOST 2012; Vol. 1 - Fedushchak T. A. Taisiya Aleksandrovna; Uimin M. Mihail; Zhuravkov S. P. Sergey Petrovich; Vosmerikov A. V. Aleksandr Vladimirovich (Section 1. Chemical engineering and "Green technology", 2012)
A new approach to manufacturing catalytic hydrotreating systems is described, which is implemented through a mechano-chemical activation of a mixture consisting of macrocrystalline molybdenum disulfide and 3d-metal nanopowders obtained by electrophysical methods. The results of investigation of new catalyst systems reactivity are reported.